LINGUISTIC CRITICISM IN ABD AL-QAHIR AL-JURJANI'S BOOK AL-MUQTASID: TOOLS AS A MODEL - Hamad, Hiyam Khalil Ibrahim; Ghani, Mona Adnan (Veredas do Direito, 2026)
This research aims to study the critical aspect of violating the rules of grammar and what the structures require according to one of the scholars of Islamic culture in all its known dimensions in his era, namely Imam Abdul Qahir Al-Jurjani (d. 471 AH). The aim of studying this topic was twofold:One aspect relates to the field of criticism, a field that highlights the author's scholarly ability and intellectual contribution, and cultivates ideas, granting them perfection and development. The second aspect relates to the text upon which the study is based; the researcher who meticulously examines the books of Imam Abdul Qahir al-Jurjani will find knowledgeexaggeratedAnd a grammatical mind that absorbed the opinions of the grammarians who preceded him, subjecting most of their opinions to criticism, aided in all of that by a grammatical mindset whose source was familiarity with the principles of the grammatical industry, from hearing and analogy and others, as is clear during this research.